2019
DOI: 10.1002/jimd.12136
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of disease‐causing variants in the Swedish galactosemia population: Identification of 16 novel GALT variants

Abstract: The aim was to determine disease‐causing variants in the GALT gene which codes for the enzyme galactose‐1‐phosphate uridylyltransferase. Loss of activity of this enzyme causes classical galactosemia—a life threatening, treatable disorder, included in the Swedish newborn screening program since 1967. A total of 66 patients with the disease are known in Sweden and 56 index patients were investigated. An additional two patients with Duarte galactosemia were included. The disease‐causing variants were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Pro163=) in ECHS1 provides some sort of advantage with respect to fitness to have become that enriched in this population. Synonymous variants have also been reported in other inborn metabolic diseases (Ohlsson et al, 2019;Salomons et al, 2007). They produce different levels of both, normal and aberrant transcripts from the same allele.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Pro163=) in ECHS1 provides some sort of advantage with respect to fitness to have become that enriched in this population. Synonymous variants have also been reported in other inborn metabolic diseases (Ohlsson et al, 2019;Salomons et al, 2007). They produce different levels of both, normal and aberrant transcripts from the same allele.…”
Section: Discussionmentioning
confidence: 92%
“…Although synonymous variants are rarely identified as disease causing there is now increasing evidence that the impact of silent mutations is vastly underappreciated. For example a recent study, investigating the mutational spectrum for galactosemia in Sweden, revealed two pathogenic silent variants (p.Pro36 = and p.Pro109=) in GALT, resulting in abnormal splicing leading to a decreased residual GALT activity and classic galactosemia phenotype (Ohlsson, Hunt, Wedell, & von Döbeln, 2019). A machine learning algorithm using a deep neural network process to more accurately predict splice junctions estimates that 10% of disease causing mutations are due to cryptic splice sites including synonymous variants (Jaganathan et al, 2019) (Strauss et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A less severe presentation of galactosemia is associated with the Duarte variant [ 138 ]. Recently, genome wide association studies conducted in Argentina [ 139 ] identified 14 different mutations among 72 unrelated alleles and similar studies conducted in Sweden [ 140 ], Greece [ 141 ], Korea [ 142 ], Turkey [ 143 ], Lithuania [ 144 ] and India [ 145 ] have reported mutations that are confined to specific regions and populations. Current approaches for the treatment of galactosemia include neonatal screening [ 146 ] followed by dietary management via the reduction or substitution of galactose and lactose; however, long-term therapy required additional interventions such as molecular chaperones to correct the misfolded [ 147 ] GALT enzyme [ 148 ] and the reliance on animal models to characterize the genetic association between GALT mutations and galactosemia [ 149 ].…”
Section: Galactosemiamentioning
confidence: 98%